2023
DOI: 10.31234/osf.io/3tjw6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Under no illusion: An acceptability study on Czech agreement attraction

Abstract: Agreement attraction has been extensively studied in many languages and in both the production and comprehension of language. In comprehension, it has been found that ungrammatical sentences such as *The key to the cabinets were rusty are often judged as grammatical due to the presence of the attractor word cabinets that matches the verbal auxiliary in number. This is not the case when the attractor word is not plural, but singular (cabinet). This illusion of grammaticality has been documented in many of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, syncretism of the attractor alone (i.e., of one not in fact plural) was not found to give rise to attraction, as opposed to what was found in Russian (Slioussar, 2018). Finally, Lacina (2023) ran a pilot acceptability study on number attraction in Czech and found no evidence of the effect in untimed Likert scale judgements. However, since the illusion of grammaticality arises mostly in speeded tasks, these data are inconclusive regarding the presence of the effect in the language.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, syncretism of the attractor alone (i.e., of one not in fact plural) was not found to give rise to attraction, as opposed to what was found in Russian (Slioussar, 2018). Finally, Lacina (2023) ran a pilot acceptability study on number attraction in Czech and found no evidence of the effect in untimed Likert scale judgements. However, since the illusion of grammaticality arises mostly in speeded tasks, these data are inconclusive regarding the presence of the effect in the language.…”
Section: Introductionmentioning
confidence: 87%
“…The authors showed that while an agreement attraction effect was clearly visible for English data, no such effect was attested for Czech translation equivalent stimuli. Moreover, an untimed acceptability judgment study on Czech (Lacina, 2023 ) also did not reveal any agreement attraction effects. It did however show that Czech comprehenders were sensitive to the agreement violations present in attraction sentences.…”
Section: Introductionmentioning
confidence: 87%